Mapeamento e utilização dos laboratórios de informática educacionais nas escolas do campo da 8ª CRE - Camillo, Cintia Moralles (2019)
The present study was carried out within the framework of the Network Educational Technologies Management line of the Postgraduate Program in Educational Network Technologies (PPGTER) of the Federal University of Santa Maria (UFSM). The objective of this study was to map the Educational Informatics Laboratories (LIEs) with regard to their existence and use as pedagogical support in the field education schools in the city of Santa Maria / RS, coordinated by the 8th Regional Educational Coordination (CRE). As for the methodology, this research is a qualitative and quantitative case study. Its technique includes the extensive direct observation carried out through questionnaires applied to the directive team, to the educators and students of the 8th CRE field schools. The collected data were categorized, compiled and had statistical treatment, in order to respond to the yearnings. The results showed that the LIEs are little used by the lack of computers, the internet signal is very weak and there is no maintenance of the computers. It was found that both educators and students access social networks daily, but they do not have knowledge about educational technologies. The presented dissertation generated as products the text presented here, since it is in the line of management, as well as based on the personal motivation of the researcher, it was proposed a notebook of pedagogical practices and the use of TDIC.